Compliance of Cypriot nurses with standard precautions to avoid exposure to pathogens - Efstathiou, Georgios; Merkouris, Anastasios; Raftopoulos, Vasilios; Papastavrou, Evridiki (My University, 2011)
Standard Precautions have been introduced as a means to protect health professionals from exposure to pathogens. This study examines the extent of Cypriot nurses' compliance with the main aspects of Standard Precautions and explores the possible associations with the nurses' characteristics. Self-completed questionnaires that examined the frequency of the implementation of Standard Precautions were distributed to a convenience sample of 668 nurses. The response rate was 89.37%. The results showed inadequate compliance with Standard Precautions. Full compliance with all the main aspects of Standard Precautions was reported by only 9.1% of the participants. Male nurses and those who had not been exposed previously to pathogens reported better compliance, in comparison to female nurses and those who had been exposed previously. Nurses who had participated previously in an educational program about Standard Precautions reported a higher frequency of implementing them than those who had not participated. The nurses' age and frequency of the implementation of Standard Precautions were found to be significantly and positively correlated. The results can be used to enhance nurses' safety by focusing on areas of non-compliance
Keywords: Nurses; Compliance; Exposure; Pathogens; Safety; Standard Precautions